Elements to consider in developing draft negotiating texts (a submission from CGIAR) - CGIAR (2024)
Submission from CGIAR further to the Plant Treaty Secretariat's call for written submissions from contracting parties and stakeholders concerning any other issues (other than the 3 ‘hotspots’ discussed in the 11th meeting of the WG-EFMLS that took place from April 15-17 2024) that the Co-chairs of the WG-EFMLS should take into consideration as they develop revised draft texts of the SMTA, Annex 1, and the draft Resolution, to be used as a basis for negotiations during the 12th meeting of the WG-EFMLS in September, 2024.